Resistance exercise recovery morphology and AQP1 expression in denervated soleus muscle of Wistar rats - Lovison, Keli (2018)
It was our objective to analyse the effects of resistance exercise (climbing steps), which was started in the acute phase, on the histomorphometry and the expression of aquaporin 1 (AQP1) in the soleus muscle after sciatic nerve injury in Wistar rats. Twenty-four adult rats were randomly divided into the following four groups, containing six animals each: control (G1); exercise (G2); injury (G3); and exercise with injury (G4). Three days after the compression of the sciatic nerve, the animals in G2 and G4 were submitted to resistance exercise for 21 non-consecutives days. The exercise was conducted in two series of 10 consecutive ascents of the ladder, with an additional weight of 100g and with an interval of 60 seconds between sets for rest. After this period, the animals were sacrificed, and the soleus muscle was processed. The number of blood capillaries in G3 was 65.7% and 76.86% higher when compared with the G2 and G4, respectively. The morphological analysis revealed muscle damage in G3, hypertrophy in G2 and significant improvement in the muscle in G4. The AQP1 was immunolocalized in the endothelium of blood capillaries present in the muscle fibres, with different expressions in the groups. Resistance exercise initiated in the acute phase was an effective therapeutic modality in the recovery of morphological aspects in the soleus muscle after denervation.